A Stylistic Analysis of W.H. Davies’ Selected Poems: Unveiling Linguistic Features in His Poetry - Malik Umer bin Ajmal; Edi Suprayetno; Muhammad Usman Abbasi (Journal of Applied Linguistics, 2024)
The purpose of this paper was to analyze William Henry Davies’ poems “The Rain”, “Money” and “The Fog” from the lens of Stylistic analysis. This analysis was done at the level of graphological, Lexico-syntactical, morphological, and phonological patterns. Stylistic analysis is used in linguistics to discover the various language features that are in the poems and create the meaning that can be found from the language features. This piece of the paper helps in understanding the stylistics according to different scholars, the basic concept of these poems that are related to life’s problems, and the stylistic techniques used in them. This comprehensive examination highlights the simplicity and accessibility of Davies’ poetry, making it relatable and profound. The findings underscore the distinction between poetic and non-poetic language, showcasing the effectiveness of stylistic analysis in literary studies. The study also underscored Davies' mastery of a straightforward yet profound poetic style, reflecting his experiences and philosophical reflections on nature and humanity. This analysis highlighted the distinct characteristics of Davies' poetic language and his unique contribution to early 20th-century poetry. Keywords : Stylistics_Analysis; Linguistics_Features; Poetry